2009
DOI: 10.1071/sr08120
|View full text |Cite
|
Sign up to set email alerts
|

Management practices for control of runoff losses from cotton furrows under storm rainfall. III. Cover and wheel traffic effects on nutrients (N and P) in runoff from a black Vertosol

Abstract: Transport of nitrogen (N) and phosphorus (P) in runoff was measured using a rainfall simulator on a cotton hill–furrow system with a range of on-ground cover (0–60%), each with and without prior wheel traffic in the furrow. Total N and P losses in runoff (kg/ha) from the bare plots on a whole-field basis (wheel and non-wheel tracks) were equivalent to 1.5% and 1%, respectively, of fertiliser applied that season (218 kg N/ha, 27 kg P/ha). This was for a single runoff event of 17 mm, about 1/10 of the total runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The furrow runoff carried more than 10% of the applied trifluralin which contrasts with data of Leonard et al (1979) that showed only a small proportion of the applied trifluralin in run-off. Total trifluralin loss in run-off was strongly related to run-off volume rather than to concentrations in that run-off because the soil sorption index for trifluralin is very high (8000 Koc) (Silburn and Glanville, 2002). Trifluralin movement in the runoff has been reported to vary greatly due to sediment load, sediment type, formulation used, amount and duration of irrigation and canopy cover than solely on the method of irrigation (Wauchope, 1978).…”
Section: Trifluralin and Simazinementioning
confidence: 99%
See 1 more Smart Citation
“…The furrow runoff carried more than 10% of the applied trifluralin which contrasts with data of Leonard et al (1979) that showed only a small proportion of the applied trifluralin in run-off. Total trifluralin loss in run-off was strongly related to run-off volume rather than to concentrations in that run-off because the soil sorption index for trifluralin is very high (8000 Koc) (Silburn and Glanville, 2002). Trifluralin movement in the runoff has been reported to vary greatly due to sediment load, sediment type, formulation used, amount and duration of irrigation and canopy cover than solely on the method of irrigation (Wauchope, 1978).…”
Section: Trifluralin and Simazinementioning
confidence: 99%
“…In spite of lower runoff from subsurface 90 and 120% ETc compared to furrow, greater prometryn movement was primarily caused by higher concentration in the runoff associated with the drip irrigation treatments. Silburn and Glanville (2002) showed that the transport of prometryn was largely in the water phase rather than in sediments from a cotton field. As the run-off from the subsurface drip irrigation contained less suspended sediment but more concentrated water than the furrow plots in our trial, it resulted in a greater amount of prometryn movement from the subsurface drip irrigation than furrow treatments.…”
Section: Fluometuron and Prometrynmentioning
confidence: 99%
“…These wheel tracks have reduced infiltration capacity, creating a small-scale variability in infiltrability; they restrict subsurface flow and increase return flow and they redirect surface runoff (Tullberg et al, 2001, Green et al, 2003, Silburn and Hunter, 2009. Tillage is intended to remove these adverse effects of wheeling and provide other positive effects, such as incorporation of residues and seeds.…”
Section: Soil Bulk Densitymentioning
confidence: 99%
“…In Queensland, Australia, zero tillage and no-traffic were observed to minimize environmental degradation effects including soil erosion while increasing grain yield. Further, the amount of rain required to initiate run-off in irrigated cotton was increased by retaining crop residues and other materials that increased soil cover while perennial pasture rotations improved soil fertility (Silburn and Glanville, 2002;Armstrong et al, 2003). Land forming for surface water drainage: Poor drainage is a major problem in Vertisols due to water logging of early planted crops; thus, universally, Vertisols are cropped post-rain season with plant growth being sustained largely by residual soil MC.…”
Section: (B) Soil Fertility Managementmentioning
confidence: 99%